Helping schools support caregivers of youth who self-injure: Considerations and recommendations - Whitlock, J.; Baetens, I.; Lloyd-Richardson, E.; Hasking, Penelope; Hamza, C.; Lewis, S.; Franz, P.; Robinson, K. (Sage Publications, 2018)
© 2018, The Author(s) 2018. Non-suicidal self-injury (NSSI) is a significant international mental health concern, with consequences for not only youth who self-injure, but for their entire family system. Helping caregivers respond productively to their child’s self-injury is a vital part of effectively addressing NSSI. This paper will assist school-based mental health practitioners and other personnel support caregivers of youth who self-injure by reviewing current literature, highlighting common challenges faced by school-based professionals, and providing evidenced-informed recommendations for supporting caregivers of youth who self-injure. We posit that schools can best support caregivers by having clear and well-articulated self-injury protocols and by engaging caregivers early. Once engaged, helping caregivers to navigate first conversations, keep doors open, know what to expect, seek support for themselves and understand and address safety concerns will ultimately benefit youth who self-injure and the school systems that support them. We also review recommendations for working with youth whose caretakers are unwilling or unable to be engaged.